Управління проектами як інструмент активізації транскордонного співробітництва - Павліха, Наталія Володимирівна; Кицюк, Ірина Василівна; Pavlikha, Nataliia V.; Kytsiuk, Iryna V. (Інститут регіональних досліджень НАН України, 2014)
У статті обґрунтовано значення транскордонного співробітництва для соціально-економічного розвитку країни та її регіонів, а також виявлено необхідність застосування управління проектами як інструмента активізації транскордонної співпраці.

The importance of transborder cooperation for social and economic development of the country and its regions is considered and the need of project management as an instrument of intensify the transborder cooperation is identified in the article. In today’s economy the most economic problems are solved with the help of some projects. Thus, the desire of border regions to effectively manage of their competitive positions requires general studies of transborder cooperation and social and economic problems of the development of these regions. As the result it should be the appearance of project decisions and justifications for their practical implementation both at national and international level.
Project management as an instrument of intensification the transborder cooperation
Keywords: прикордонні регіони; конкурентоспроможність; транскордонне співробітництво; національна економіка; проект; управління проектами; border regions; transborder cooperation; competitiveness; national economy; project; project management